The Pilagá of the Argentine Chaco through an exoticizing and ethnographic lens : the swedish documentary film following indian trails by the pilcomayo river - Gustavsson, Anne Thérése Ellen (2013)
In this article, we explore how traveling relates to image production and how transcultural filmic representations both uphold and are sustained by a "coloniality of seeing." We pay special attention to the historical conditions of film making in an expedition context and the expectations associated with early film in Sweden. We discuss this through the study of the documentary film Following Indian Trails by the Pilcomayo River, which was recorded during a Swedish expedition to the Argentine Chaco in 1920 and later released in Stockholm in 1950 during a private screening organized by the Swedish Chaco Travellers Association. We argue that the film presents an account inspired by classic ethnography which rescues and puts into circulation images of indigenous people from the "impenetrable" and "savage" Chaco. The ethnographic emphasis in the narrative seems to have shifted with time as it was probably only partly present during the shooting of the footage. In the narrative mode of "monstration," when bodies meet machines "in the field," native performances are presented as an "unstaged" and realist spectacle. Later in the 1950 "macro-narration," encompassing the final cutting and editing of the original footage, fragments of spectacle are systematized into an ethnographic description of primitive life.